2021
DOI: 10.1016/j.intimp.2021.107988
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of macrophage polarization by hypoxia-PADI4 coordination in Rheumatoid arthritis

Abstract: Background: Hypoxia, a common feature of rheumatoid arthritis (RA), induces the overexpression of peptidyl arginine deiminase 4 (PADI4) in broblast-like synoviocytes (FLSs) and macrophages. However, the roles of PADI4 and its inducer hypoxia in the regulation of macrophage polarization remain unclear.This study aimed to investigate the role of hypoxia-PADI4 for macrophage polarization in RA patients.Methods: synovial tissue(ST) and synovial uid(SF) were collected from 3 OA patients and 6 RA patients.The distri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…They are found in a wide range of cells and tissues, among which PADI4 is found in macrophages, monocytes, granulocytes and cancer cells [18] . Some studies have found that PADI4 is closely related to the pathogenesis of various tumors and rheumatoid arthritis (RA) [18,19] . Cheng et al found that hypoxia related PADI4 is related to the classical activation (M1) of macrophages, reducing the expression of PADI4 and improving the hypoxia environment, in ammatory reaction can be alleviated, especially in RA [19] .…”
Section: Discussionmentioning
confidence: 99%
“…They are found in a wide range of cells and tissues, among which PADI4 is found in macrophages, monocytes, granulocytes and cancer cells [18] . Some studies have found that PADI4 is closely related to the pathogenesis of various tumors and rheumatoid arthritis (RA) [18,19] . Cheng et al found that hypoxia related PADI4 is related to the classical activation (M1) of macrophages, reducing the expression of PADI4 and improving the hypoxia environment, in ammatory reaction can be alleviated, especially in RA [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other stimuli such as hypoxia and metabolic intake have also been linked to macrophage polarization. While M1 macrophages are normally found in normoxic tumor regions, the M2 macrophages are present in hypoxic conditions of the tumor [ 53 , 54 ]. The discovery of new stimuli and their effect on macrophage polarization suggests the need for using a combination of markers for defining a specific activation state of macrophages, rather than using the nomenclature of M1/M2 phenotypes.…”
Section: Glioma Immune Landscapementioning
confidence: 99%
“…In macrophages, PADI2 can promote the expression of IL-1β, IL-6 and TNF-α through the citrullination of NF-κB p65 ( 69 ). PADI4 can positively regulate TNF-α and CCL2 ( 70 ). PADI2 coordinates with PADI4 to regulate the assembly of the NLRP3 inflammasome to promote IL-1β release ( 71 ).…”
Section: Physiological Processes Involving the Padi Familymentioning
confidence: 99%